Hapten synthesis and production of specific antibody against 3-amino-5-morpholinomethyl-2-oxazolidone for immunoassay without derivatisation. Issue 1 (1st January 2018) - Liu, Fengyin; Chen, Zijian; Shen, Yudong; Sun, Yuanming; Yang, Jinyi; Wang, Hong; Lei, Hongtao; Xu, Zhenlin
ABSTRACT: Immunoassay direct for 3-amino-5-morpholinomethyl-2-oxazolidone (AMOZ), the metabolite of furaltadone, based on a specific antibody was usually unavailable due to its small molecule weight. In this work, a hapten with a double bond and an active carboxyl group was designed and then conjugated to peptide dendrimer to obtain novel multiple haptens. The haptens and multiple haptens were coupled to bovine serum albumin as immunogens. Polyclonal antibodies showed binding to free AMOZ in a heterologous competitive indirect enzyme-linked immunosorbent assay were obtained. The assay showed IC50 (half maximal inhibitory concentration) of 4.1 μg/kg and limit of detection of 0.2 μg/kg for AMOZ. Recoveries of AMOZ from grass carp were tested from 83.1% to 117.0%, with the coefficient of variation below 12%. As no laborious derivatisation procedure was employed, the proposed assay should be useful for the screening of AMOZ for a large number of samples.